Location Quotient Analysis in Facing Economic Competition during Covid-19 Pandemic - Lienggar Rahadiantino; Juniarun Fathurrohman (JURNAL SOSIAL HUMANIORA (JSH), 2021)
The Covid-19 pandemic has had a significant impact on people's lives. The economic sector is so affected that a balanced and well-targeted policy is needed to overcome the difficulties arising from the pandemic. Large-Scale Social Restrictions (PSBB) which has been intended to reduce the spread of Covid-19 indirectly makes economic activities in production, consumption, and distribution to be hampered, so to speak, cause an economic contraction. The national economy was contracted by 5.32 percent (y-o-y) and the economy of East Java was contracted 5.90 percent (y-o-y) in the second quarter of 2020. Nevertheless, there are several economic sectors that still have good performance and have contributed greatly to East Java's Gross Regional Domestic Product. Using Location Quotient (LQ) analysis, this study aims to identify basic sectors and formulate the composition and shift of the basic sectors by using GRDP as an indicator of regional growth